PHONOLOGICAL STUDY OF MANDAILING AND ANGKOLA LANGUAGES IN NORTH SUMATRA - Harianto II Harianto II; Zulfitri Zulfitri; Teguh Satria Amin (Universitas Majalengka, 2020)
This research aims to describe and also explain the study of phonology in the Mandailing and Angkola languages of North Sumatra. A qualitative descriptive research method was used in research on the phonology of the Angkola and Mandailing languages. Scientific steps were carried out by collecting data by preparing a basic vocabulary from Morris Swadesh of 200 words. Then the observation step of the data obtained, the feasibility test of the data as well as the transcription and also the feasibility test became one of the steps carried out in the research. In data analysis, there are several steps such as data comparison, data analysis and also sound changes that occur from the presentation of the analysis results. The theoretical study that forms the basis of this research is a comparative historical linguistic study which forms the basis of Keraf (1996). From these data, several sound changes were obtained which had the form of metathesis, syncope, apocope, apheresis, prosthesis, and also paragog and epenthesis.